Small-Molecule Hormones: Molecular Mechanisms of Action - Monika Puzianowska-Kuznicka; Eliza Pawlik-Pachucka; Magdalena Owczarz; Monika Budzińska; Jacek Polosak (International Journal of Endocrinology)
Small-molecule hormones play crucial roles in the development and in the maintenance of an adult mammalian organism. On the molecular level, they regulate a plethora of biological pathways. Part of their actions depends on their transcription-regulating properties, exerted by highly specific nuclear receptors which are hormone-dependent transcription factors. Nuclear hormone receptors interact with coactivators, corepressors, basal transcription factors, and other transcription factors in order to modulate the activity of target genes in a manner that is dependent on tissue, age and developmental and pathophysiological states. The biological effect of this mechanism becomes apparent not earlier than 30–60 minutes after hormonal stimulus. In addition, small-molecule hormones modify the function of the cell by a number of nongenomic mechanisms, involving interaction with proteins localized in the plasma membrane, in the cytoplasm, as well as with proteins localized in other cellular membranes and in nonnuclear cellular compartments. The identity of such proteins is still under investigation; however, it seems that extranuclear fractions of nuclear hormone receptors commonly serve this function. A direct interaction of small-molecule hormones with membrane phospholipids and with mRNA is also postulated. In these mechanisms, the reaction to hormonal stimulus appears within seconds or minutes.